Students’ Perception of Digital Texts Reading: A Case Study at the English Education Department of Universitas Kristen Indonesi - Manalu, Benny Hinn (JET (Journal of English Teaching), 2019)
This study was conducted to explore students' perceptions of reading digital texts. To attain the objective, the data were collected through an online questionnaire uploaded in Google Form and an interview. The questionnaire was intended to collect quantitative data concerning the participants’ responses about their interest and motivation, digital text reading efficacy, problems in digital text reading, and preference towards digital or printed text reading. The participants of the study were 65 English pre-service teachers selected from the whole students of the English Education Department of Universitas Kristen Indonesia in the academic year 2019/2020, and the sample was 65 participants. The collected data were analyzed descriptively using Microsoft excel. The findings revealed that the participants perceived digital texts reading positively. They preferred reading digital texts because they were motivating, interesting, and suite their expected way of reading. The main problem they encountered in reading digital texts was due to the screen light which could irritate their eyes.